Safety Performance at Proton Warehouse Parts Centre Sdn Bhd in Shah Alam, Selangor - Prabakaran, Munusamy (2023)
Workplace safety and health are integral components of organisational governance, with significant implications for employees and businesses alike. This study investigates safety performance among warehouse employees at Proton Parts Centre Sdn Bhd, Shah Alam, Malaysia. It explores the connections between safety concerns, safety policy, safety motivation, and performance within the warehouse setting, aiming to provide insights into factors influencing safety performance and areas for improvement. The study utilises a range of data collection methods to assess various aspects of safety performance comprehensively. The correlation analysis results indicated that there is a significant relationship among all variables. Safety concern, safety policy and safety motivation were found to have a significant relationship with safety performance. Safety concern showed a positive level of relationship with a correlation coefficient value of r = 0.84. On the other hand, safety policy and safety motivation exhibited indicating a strong positive relationship with correlation coefficient values of r= 0.82 and r = 0.80, respectively. Findings from this research are expected to contribute to enhancing safety practices, guide management in improving safety management, and extend the existing knowledge in the field of occupational safety and health. However, it's essential to acknowledge that the research has geographical and methodological limitations that should be considered when applying the findings to other contexts.